Gastrointestinal stromal tumour in Meckel's diverticulum - Chandramohan, K (BioMed Central, 2007)
BACKGROUND: Meckel's Diverticulum is the most commonly encountered congenital anomaly of the small intestine, occurring in approximately 2% of the population. Occasionally Meckel's diverticulum harbors neoplasms. CASE PRESENTATION: A 65 year old gentleman, presented with a pelvic mass. On exploratory laparotomy, it turned out to be gastrointestinal stromal tumour (GIST) arising from Meckel's diverticulum. Short history and review of literature are discussed. CONCLUSION: Neoplasms occurring from Meckel's diverticulum, even though rare, should be considered as differential diagnosis of pelvic masses arising from bowel, wherever imaging modalities fail to give a definitive diagnosis.